Association between chest compression rates and clinical outcomes following in-hospital cardiac arrest at an academic tertiary hospital. (January 2017) - Kilgannon, J. Hope; Kirchhoff, Michael; Pierce, Lisa; Aunchman, Nicholas; Trzeciak, Stephen; Roberts, Brian W.
Abstract: Aims: Recent guidelines for management of cardiac arrest recommend chest compression rates of 100–120 compressions/min. However, animal studies have found cardiac output to increase with rates up to 150 compressions/min. The objective of this study was to test the association between chest compression rates during cardiopulmonary resuscitation for in-hospital cardiac arrest (IHCA) and outcome. Methods: We conducted a prospective observational study at a single academic medical center. Inclusion criteria: age ≥ 18, IHCA, cardiopulmonary resuscitation performed. We analyzed chest compression rates measured by defibrillation electrodes, which recorded changes in thoracic impedance. The primary outcome was return of spontaneous circulation (ROSC). We used multivariable logistic regression to determine odds ratios for ROSC by chest compression rate categories (100–120, 121–140, >140 compressions/min), adjusted for chest compression fraction (proportion of time chest compressions provided) and other known predictors of outcome. We set 100–120 compressions/min as the reference category for the multivariable model. Results: We enrolled 222 consecutive patients and found a mean chest compression rate of 139 ± 15. Overall 53% achieved ROSC; among 100–120, 121–140, and >140 compressions/min, ROSC was 29%, 64%, and 49% respectively. A chest compression rate of 121–140 compressions/min had the greatest likelihood of ROSC, odds ratio 4.48 (95% CI 1.42–14.14). Conclusions: In this sample of adult IHCA patients, a chest compression rate of 121–140 compressions/min had the highest odds ratio of ROSC. Rates above the currently recommended 100–120 compressions/min may improve the chances of ROSC among IHCA patients.